ANALISIS POTENSI EKOWISATA HEART OF BORNEO DI TAMAN NASIONAL BETUNG KERIHUN DAN DANAU SENTARUM KABUPATEN KAPUAS HULU - Erni Yuniarti; Rinekso Soekmadi; Hadi Susilo Arifin; Bambang Pramudya Noorachmat (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2018)
Betung Kerihun National Park (TNBK) and Danau Sentarum National Park (TNDS) is one of the Conservation District that directly adjacent to neighboring Malaysia and as a form of Transboundary Conservation Area (TBCA) between Indonesia and Malaysia. This national park is also included in the National Tourism Strategic Area (KSPN) and becomes one of the three Destination Management Organization of the Ministry of Tourism of the Republic of Indonesia as well as the National Tourism Destination. Tourism sector, particularly ecotourism can be used as the spearhead and even become a leading sector in increasing the potential of PAD. This study aims to analyze the tourism potential and attractions of attraction in two national parks and determine the feasibility in ecotourism development. This research was using descriptive research, with approach using analysis of tourism potency and object of natural tourist attraction (Obyek Daya Tarik Wisata Alam/ODTWA). The results show that TNBK and TNDS is feasible to be developed as ecotourism destination based on the recapitulation of potential value of objects and natural attractions attraction with a potential value index of 78.20%. Some criteria that require attention and improvement are accessibility and accommodation, so it can be a priority if this national park area developed into ecotourism destination.